Analysis of Samsung’s Strategy in Dealing With Global Market Competition in International Business - Putra, Edy Yulianto; Putri, Inda Meyllya; Mahendra, Rizky Adi; Sibagariang, Michael Iken Bonar Anju; Mey, Nabila Arinov; Kusumo, Pradino; Hutagalung, Rince Monica (TALENTA Publisher, Universitas Sumatera Utara, 2023)
This study aims to analyze Samsung's strategy in facing global market competition in international business. The research method applied in this study is the Secondary Data Analysis (ADS) method, which is in the form of using and analyzing existing data without having to conduct surveys and interviews. The results of this study are the marketing, global and international strategies implemented by the Samsung company.